Design and Implementation of an Intelligent Glove for Individuals with Speech and Hearing Impairments - Ali, Wafaa Hassan; Suleiman, Ola Riyadh; Fathel, Lina Akram; Ali, Ghadeer Hussein (American Journal of Botany and Bioengineering, 2025)
Individuals with speech and hearing impairments encounter communication obstacles in daily interactions due to an absence of widely accessible technology. However, technological advancements now enable the design and implementation of systems in a cost-effective manner to address this communication challenge. This study focuses on developing a user-friendly interface tailored to the needs of such individuals—a key objective remains to reconcile the intricate requirements of the speech and hearing impaired community with contemporary technology. In response, an intelligent glove serves as a cost-effective, innovative communication aid. The glove functions as an input device featuring sensors, while an accompanying mobile application provides real-time display of recognized data on a smartphone. Thus, speech and hearing impaired users can engage in streamlined interactions with the surrounding world via the glove and mobile app before an intermediary. Detailed design requirements capture the user perspective to guide the implementation of the intelligent glove. Looking ahead, the ongoing development of this innovative communication system promises enhanced accessibility and engagement for speech and hearing impaired individuals, paving the way for a more inclusive society.